Direct monitoring of reaction intermediates through in situ characterization to promote the selectivity of N-integrated electrocatalytic CO2 reduction - Zhixuan Chen; Ying Wang (Fundamental Research)
Energy-intensive chemical manufacturing is one of the largest contributors to global CO2 emissions. With the vigorous development of renewable energy, the electrocatalytic CO2 reduction reaction (CO2RR) has become a sustainable technology for recycling. To broaden the variety of products, the N-integrated electrocatalytic CO2RR (NCO2RR) constructs a new element conversion pathway by introducing nitrogen upon CO2RR. However, the product selectivity of NCO2RR is still very low, which seriously restricts its practical application. In recent years, an increasing amount of research has focused on upgrading the performance of NCO2RR. Accurate understanding of its catalytic mechanism, that is, obtaining online information about reaction intermediates by in situ characterization techniques, can guide the optimization of electrocatalytic systems. Currently, this method makes great contributions in the field of electrocatalysis, including NCO2RR mechanism research. This review briefly summarizes the research status and existing reaction intermediates of NCO2RR and explains how the investigation of intermediates can improve electrocatalytic selectivity. Meanwhile, the application of in situ characterization techniques for analyzing different types of intermediates in NCO2RR and its related fields are emphasized in this review. The significant value of these technologies in revealing electrocatalytic mechanisms can help improve electrocatalytic selectivity, allowing for future optimization of NCO2RR.